NEW VIEWS ON THE INTERPRETATION OF THE IMAGE OF ZAID ZAKHAB IN THE EPIC OF ALISHER NAVOI "SABAI SAYYAR" - Akmalovich, Umarov Sardorbek (Scholar Express Journals, 2021)
The article analyzes in a new way "The story of Zaid Zakhab, who came from the second climatic road" in the epic of Alisher Navoi "Sabai Sayyar". We interpreted Zaid not only as a lying thief, but also as a brave person who draws conclusions from mistakes and goes on the right path. The work harmoniously uses the ideas and colors of the fearlessness. We emphasize that yellow, which represents the state of mind of Zayed, not only in the sense of precious gold, but also in the sense of faith, which is sacred in gold.
Keywords: fearlessness; courage; bravery; the image of faith Zayd; Constantinople; colors